Method Development And Validation For The Torsemide In Tablet Dosage Form By Rp-Hplc (Journal of Pharmaceutical Negative Results, 2022)
For the purpose of determining Torsemide, a straight forward reverse-phase liquid chromatography method has been created and subsequently validated. In order to achieve a pH of 3.5, Ortho-phosphoric acid was used in the buffer. The mobile phase was used in a ratio of 40:60% v/v of phosphate buffer and acetonitrile. The column used was X Terra C8 (4.6 x 150 mm, 3.5 mm ID), and DAD detection at 288 nm was used at a flow rate of 0.8 ml/min. For the Torsemide assay, the technique was linear over the concentration range of 50 to 100 µg/ml. Torsemide had a retention time of 2.406 mins. The analysis's findings were verified using recovery tests and statistical analysis. Torsemide's detection limit (LOD) & quantitation limit (LOQ) and were found to be 2.91µg/ml and 10.1µg/ml, respectively. The study's findings demonstrated the usefulness of the suggested RP-HPLC method for the routine measurement of Torsemide in bulk medication and in its pharmaceutical dose form.